Functional circuits of new neurons in the dentate gyrus - Vivar, Carmen; Van Praag, Henriette (Frontiers in Neural Circuits, 2013)
The hippocampus is crucial for memory formation. New neurons are added throughout life to the hippocampal dentate gyrus (DG), a brain area considered important for differential storage of similar experiences and contexts. To better understand the functional contribution of adult neurogenesis to pattern separation processes, we recently used a novel synapse specific trans-neuronal tracing approach to identify the (sub) cortical inputs to new dentate granule cells. It was observed that newly born neurons receive sequential innervation from structures important for memory function. Initially, septal-hippocampal cells provide input to new neurons, followed after about one month by perirhinal and lateral entorhinal cortex. These cortical areas are deemed relevant to encoding of novel environmental information and may enable pattern separation. Here, we review the developmental time-course and proposed functional relevance of new neurons, within the context of their unique neural circuitry.